Modeling of rotary movement of the articulating crane with increased gaps in the hinge joints of the links - Lagerev I.A.; Milto A.A.; Lagerev A.V. (Научно-технический вестник Брянского государственного университета)
The article made computer simulation of dynamics of hydraulic articulating cranes with fully rotary motion for the case when the cylindrical hinges have an increased gap. Considered the use of special damping devices to reduce shock loads due to the presence of increased gaps. In previously developed software package KBCrane performed a series of calcu-lations made it possible to establish the relationship between the stiffness and damping devices the effectiveness of their use in varying the magnitude of the gap. In the case of the rotary movement of the articulating crane, a comparative analysis of work of joints of the connection node of the boom and lifting device with no gap and with high gaps. The features of the damping devices work joints and cushioning. Conclusions on positive and negative sides of the use of elastic damping devices.